PENERAPAN PEMBELAJARAN BERDIFERENSIASI UNTUK MENINGKATKAN KEMAMPUAN MEMBACA PADA MATA PELAJARAN BAHASA INDONESIA DI KELAS IV SD NEGERI 243/VI BUNGO TANJUNG - Ed Wardani; Laila Purwasari Ning Wulan (Sosio Akademika: Journal of Sosial Sciences and Islamic Studies, 2025)
This research was conducted to evaluate how effective differentiated instruction is in enhancing the reading abilities of fourth-grade students at SD Negeri 243/VI Bungo Tanjung. The study utilized a classroom action research (CAR) approach, implemented across two cycles of learning. The study involved 12 students from the fourth grade. Data collection methods included reading assessments, classroom observations, interviews, and document reviews. Findings showed a notable improvement in students’ reading performance after applying differentiated instruction, with average reading scores rising from 50% in the initial cycle to 75% in the subsequent cycle. Additionally, the learning environment became more dynamic, and students demonstrated increased enthusiasm toward learning. These results suggest that differentiated instruction effectively supports the development of reading skills among fourth graders at SD Negeri 243/VI Bungo Tanjung.